Colchicine treatment can improve outcomes of coronavirus disease 2019 (COVID‐19): A systematic review and meta‐analysis. (14th March 2021) - Hariyanto, Timotius Ivan; Halim, Devina Adella; Jodhinata, Claudia; Yanto, Theo Audi; Kurniawan, Andree
Abstract: Currently, there is no widely acceptable and proven effective treatment for coronavirus disease 2019 (COVID‐19). Colchicine has been shown to offer a benefit in reducing the inflammation in several inflammatory diseases. This study aims to analyze the efficacy of colchicine administration and outcomes of COVID‐19. We systematically searched the PubMed and Europe PMC database using specific keywords related to our aims until January 29, 2021. All articles published on COVID‐19 and colchicine treatment were retrieved. The quality of the study was assessed using the Newcastle–Ottawa Scale (NOS) tool for observational studies and Revised Cochrane risk‐of‐bias tool for randomized trials (RoB 2) for clinical trial studies. Statistical analysis was done using Review Manager 5.4 software. A total of eight studies with 5778 COVID‐19 patients were included in this meta‐analysis. This meta‐analysis showed that the administration of colchicine was associated with improvement of outcomes of COVID‐19 [OR 0.43 (95% CI 0.34–0.55), p  < 0.00001, I 2  = 0%, fixed‐effect modelling] and its subgroup which comprised of reduction from severe COVID‐19 [OR 0.44 (95% CI 0.31–0.63), p  < 0.00001, I 2  = 0%, fixed‐effect modelling] and reduction of mortality rate from COVID‐19 [OR 0.43 (95% CI 0.32–0.58), p  < 0.00001, I 2  = 0%, fixed‐effect modelling]. Our study suggests the routine use of colchicine for treatment modalities of COVID‐19 patients. More randomized clinical trial studies are still needed to confirm the results from this study.